2004
DOI: 10.1152/ajpheart.00808.2003
|View full text |Cite
|
Sign up to set email alerts
|

Effect of glycocalyx on shear-dependent albumin uptake in endothelial cells

Abstract: The glycocalyx layer on the surface of an endothelial cell is an interface barrier for uptake of macromolecules, such as low-density lipoprotein and albumin, in the cell. The shear-dependent uptake of macromolecules thus might govern the function of the glycocalyx layer. We therefore studied the effect of glycocalyx on the shear-dependent uptake of macromolecules into endothelial cells. Bovine aorta endothelial cells were exposed to shear stress stimulus ranging from 0.5 to 3.0 Pa for 48 h. The albumin uptake … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
57
1
1

Year Published

2007
2007
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 72 publications
(64 citation statements)
references
References 39 publications
3
57
1
1
Order By: Relevance
“…Accordingly, an albumin-containing perfusate should ‘hook’ into this structure, transmitting shear stress to the vessel wall, while artificial colloids like HES, figuratively speaking, brush only against the top of the glycocalyx molecules [38]. Such a difference is reflected by the similarity in intravascular distribution spaces of HES and red blood cells in vivo, as opposed to those tracers binding to albumin [39, 40]. This interpretation is also in line with our previous work concerning the barrier function of the EG [4, 8, 17], which is also overproportionally enhanced by albumin versus HES [8].…”
Section: Discussionmentioning
confidence: 99%
“…Accordingly, an albumin-containing perfusate should ‘hook’ into this structure, transmitting shear stress to the vessel wall, while artificial colloids like HES, figuratively speaking, brush only against the top of the glycocalyx molecules [38]. Such a difference is reflected by the similarity in intravascular distribution spaces of HES and red blood cells in vivo, as opposed to those tracers binding to albumin [39, 40]. This interpretation is also in line with our previous work concerning the barrier function of the EG [4, 8, 17], which is also overproportionally enhanced by albumin versus HES [8].…”
Section: Discussionmentioning
confidence: 99%
“…Vink & Duling (2000) demonstrated that, for anionic molecules, in addition to size, the electric charge has a profound effect on the penetration rate into the EGL. Using cultured endothelial cells, Ueda et al (2004) showed that the albumin uptake for the endothelial cells with a neutralized (no charge) EGL was almost twice that of cells with charged EGL.…”
Section: Introductionmentioning
confidence: 99%
“…Controversy exists also with respect to the dimensions of the glycocalyx on cultured endothelial cells. Findings range from Ϸ40 nm 19 to 2000 nm. 20 The findings of Potter and Damiano even suggest that cultured human umbilical vein endothelial cells (HUVECs) may be devoid of a glycocalyx.…”
mentioning
confidence: 99%